Analysis and Design of a Petty Cash Fund Accounting Information System Using a Fixed Fund System at Cv. Yoga Solafide Finance - Sri Alima (Journal of Computer Science and Research (JoCoSiR), 2023)
Currently a computer application system is needed to facilitate work. With this application, we can process the data we have to produce information that is definitely better and more useful for certain needs. But not infrequently there are several companies or agencies such as CV. Yoga Solafide who still hasn't implemented this in their performance process such as processing costs such as petty cash funds so that generating information takes quite a long time and sometimes errors occur due to the absence of a special system for processing petty cash fund data on CV. Solafide Yoga